ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI GEN-Z DALAM PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) SEBAGAI TEKNOLOGI PEMBAYARAN DIGITAL - Adinda, Meitry (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
In the midst of increasing growth in financial technology companies that act as Payment System Service Providers (PJSP) in Indonesia continue to innovate, the presence of the Quick Response Code Indonesian Standard (QRIS) acts as a solution to perfect innovation in the payment system offered by the fintech company. One of the user groups who are the main targets are Generation Z or Gen-Z because they have characteristics that are more active and literate with technological developments, and tend to be consumptive. So, this research aims to analyze the effects of Financial Literacy, Perceived Usefulness, Perceived Ease of Use, and Promotion and Advertising on Gen-Z's decision to use QRIS. This type of research is a quantitative research using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) data analysis. The data were obtained by distributing questionnaires to 250 respondents born in 1997-2004 who were students at the university in Malang Region. The results indicate that Financial Literacy, Perceived Usefulness, Perceived Ease of Use, and Promotion and Advertising significantly on Gen-Z's decision to use QRIS.